Karakteristik Minyak Atsiri dari Limbah Kulit Jeruk Keprok (Citrus reticulata) - Utami, Dwi Retnaningtyas; Prayitno, Sutrisno Adi; Hasanah, Khomarul Maulidatul (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
In this study, the selection of water and steam distillation method to extract orange peel essential oil was motivated by concerns about environmentally unfriendly extraction methods. The physical and chemical characteristics of orange peel essential oil were analyzed to assess its potential as a sustainable resource. The extraction process was optimized, and the ideal condition determined was 3 hours of extraction time at 80°C. Analysis of orange peel essential oil produced a colorless essential oil with L* values ​​of 88.80; a* -2.70 and b* -13.02 with a specific gravity of 0.849, a refractive index of 1.474, solubility in 90% ethanol is 1:1 (clear), acid value of 1.82 g/mL and ester value of 10.37 g/mL. Sensory evaluation was carried out with odor and appearance (visual) attributes. It has a distinctive aodor of fresh and sweet citrus fruit with a consistency that is not thick. These findings have significant implications that orange peel essential oil can be used in various industrial processes to produce other valuable products. Keywords: Evaluation sensory; Essential oil extraction; Agricultural waste; Volatile compounds; Physicochemical properties